Synthesis and characterization of diacylgermanes: persistent derivatives with superior photoreactivity. Issue 34 (11th August 2021) - Püschmann, Sabrina D.; Frühwirt, Philipp; Müller, Stefanie M.; Wagner, Stefan H.; Torvisco, Ana; Fischer, Roland C.; Kelterer, Anne-Marie; Griesser, Thomas; Gescheidt, Georg; Haas, Michael
Abstract : A series of novel diacylgermanes with bulky mesityl groups by the multiple silyl abstraction methodology, avoiding the Corey–Seebach reaction were synthesized. Abstract : Acylgermanes are known as highly efficient photoinitiators. In this contribution, we present the synthesis of new diacylgermanes 4a–e via a multiple silyl abstraction methodology. The method outperforms the state-of-the-art approach (Corey–Seebach reaction) towards diacylgermanes in terms of group tolerance and toxicity of reagents. Moreover, these compounds are decorated with bulky mesityl groups in order to improve their storage stability. The isolated diacylgermanes were characterized by multinuclear NMR-, UV-Vis spectroscopy and X-ray crystallography, as well as photolysis experiments (photobleaching) and photo-DSC measurements (photopolymerization behavior). Upon irradiation with an LED emitting at 385 nm, all compounds except for 4a and 4c bleach efficiently with quantum yields above 0.6. Due to their broad absorption bands, the compounds can be also bleached with blue light (470 nm), where especially 4e bleaches more efficiently than Ivocerin®.